A sodium ion precursor material and its preparation method and use

By introducing nickel iron copper aluminum hydroxide precursor material into the positive electrode material of sodium ion battery, the synergistic effect of coprecipitation method and copper and aluminum elements is used to solve the problem of prone to cracking of the structure of the positive electrode material, and its cyclic performance and electrochemical performance are significantly improved.

CN116354417BActive Publication Date: 2025-04-18JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF -1 Cites -1 Cited by

Patent Information

Application Number
CN202310418185.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-19
Publication Date
2025-04-18
Estimated Expiration
2043-04-19

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials are prone to cracking during long-term charge and discharge cycles, resulting in poor cycle stability and electrochemical performance, limiting their application.

Method used

Nickel-iron-copper-aluminum hydroxide precursor material is prepared by co-precipitation method, copper and aluminum elements are introduced to enhance the air stability and crystal structure stability of the material, thereby obtaining a layered oxide positive electrode material with good stability.

Benefits of technology

The circulation and electrochemical properties of the positive electrode material are improved, and the capacity retention rate after 200 cycles can reach more than 89.1%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention provides a sodium ion precursor material, its preparation method, and its applications. The sodium ion precursor material comprises nickel-iron-copper-aluminum hydroxide. The nickel-iron-copper-aluminum hydroxide precursor material provided by this invention has a uniform elemental distribution. The introduction of copper and aluminum into the precursor improves both air stability and crystal structure stability, thereby yielding a layered oxide cathode material with good stability and enhancing the cycle performance of the cathode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries and relates to a sodium ion precursor material and a preparation method and application thereof. Background Art

[0002] With the continuous increase in the use of lithium-ion batteries, the prices of key materials for lithium-ion batteries such as lithium, nickel, and cobalt continue to rise. Price factors have limited the development of lithium-ion batteries to a certain extent. Sodium-ion batteries are currently recognized as one of the more ideal alternative energy sources for lithium-ion batteries. On the one hand, sodium and lithium belong to the same main group and have similar physical and chemical properties and electrochemical reaction mechanisms. On the other hand, compared with lithium-ion batteries, sodium-ion batteries have the advantages of abundant resources, low prices, and wide distribution. Therefore, sodium-ion batteries have gradually become a research hotspot in the field of energy storage. Because sodium ions have a large ionic radius and a slow kinetic rate, it is difficult for sodium ions to be embedded and deintercalated in the positive electrode material, and the capacity of the positive electrode material will determine the overall cell capacity of the sodium-ion battery. Therefore, the preparation of sodium-ion battery positive electrode materials with better performance is of great significance to promote the commercial application of sodium-ion battery positive electrode materials.

[0003] Layered metal oxide positive electrode materials are currently a common sodium ion positive electrode material. At present, layered transition metal oxide materials are mainly prepared by a high-temperature solid phase method, in which sodium salt and transition metal oxide are mixed and sintered at high temperature. For example, CN107403915A discloses a manganese-based positive electrode material for a sodium ion battery, and its preparation method includes the following steps: mixing sodium salt, manganese oxide, titanium dioxide and other metal oxides and then pressing them into sheets, and then calcining them at 700-1100°C to obtain the manganese-based positive electrode material for the sodium ion battery. However, the product obtained by this traditional method has a mixed phase and forms secondary polycrystalline particles of nanoparticle agglomeration. Due to the large specific surface area and more side reactions, the secondary particle structure is prone to cracking and damage during the long-term charge and discharge cycle, thereby reducing the cycle stability performance, which seriously limits its application in sodium ion battery positive electrode materials.

[0004] Layered oxide positive electrode materials can also be obtained by coprecipitation. A sodium ion positive electrode material precursor is obtained by coprecipitation, and then the precursor is calcined with sodium salt at high temperature to obtain a layered positive electrode material with uniform element distribution, good sphericity and excellent electrochemical performance. However, the positive electrode materials currently reported to be obtained by coprecipitation are mainly nickel-iron-manganese ternary materials (NiFeMn). For example, CN114956202A discloses a precursor of a sodium ion positive electrode material with a chemical formula of Ni x Fe y Mn 1-x-y(OH)2, the preparation method includes: 1. preparing a mixed solution of Ni, Fe and Mn salts; preparing sodium hydroxide or potassium hydroxide solution as a precipitant; preparing an ammonia solution as a complexing agent; preparing an additive solution; 2. introducing a protective gas into the system, adding the mixed solution, precipitant, complexing agent and additive solution into the kettle for co-precipitation, and stopping the liquid feeding when the particle size grows to the target; 3. filtering, washing and drying the product to obtain a precursor of the positive electrode material for a sodium ion battery. The positive electrode material for a sodium ion battery is obtained by pre-sintering the precursor to obtain nickel-iron-manganese oxide, and then mixing the nickel-iron-manganese oxide with sodium carbonate and performing secondary sintering. However, during the preparation of the nickel-iron-manganese-based sodium ion battery layered oxide positive electrode material containing manganese elements, due to Mn 3+ The "Jiang-Taylor effect" will cause the octahedron of TM-O to be distorted, causing the crystal structure to be distorted, thereby affecting the electrochemical properties of the material.

[0005] Therefore, how to obtain a layered oxide positive electrode material with stable structure and excellent electrochemical performance is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a sodium ion precursor material and a preparation method and use thereof. The nickel-iron-copper-aluminum hydroxide precursor material provided by the present invention has uniform element distribution, and copper and aluminum are introduced into the precursor, which improves the air stability and the stability of the crystal structure, thereby obtaining a layered oxide positive electrode material with good stability, and improving the cycle performance of the positive electrode material.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a sodium ion precursor material, wherein the sodium ion precursor material comprises nickel-iron-copper-aluminum hydroxide.

[0009] The nickel-iron-copper-aluminum hydroxide precursor material provided by the present invention has uniform element distribution, and the nickel-iron-copper-aluminum elements cooperate and interact with each other. The valence change of copper is used to increase the capacity of the material and improve the air stability of the material. The introduction of the aluminum element can stabilize the lattice framework structure of the precursor material, thereby obtaining a layered oxide positive electrode material with good stability, thereby improving the cycle performance of the positive electrode material.

[0010] In the present invention, nickel, iron, copper and aluminum elements cooperate with each other, and aluminum and copper elements must exist at the same time. If the precursor material does not contain copper elements, the material capacity will be reduced, and if it does not contain aluminum elements, the structural stability of the material will be affected.

[0011] Preferably, the chemical formula of the nickel-iron-copper-aluminum hydroxide is Ni a Fe b Cuc Al d (OH)2, wherein 0.3≤a≤0.8, 0<b≤0.5, 0<c≤0.5, 0<d≤0.3, a+b+c+d=1.

[0012] For example, a may be 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, b may be 0.001, 0.005, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5, c may be 0.001, 0.005, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5, and d may be 0.001, 0.005, 0.01, 0.05, 0.1, 0.15, 0.2, 0.25 or 0.3, etc.

[0013] Preferably, the Ni a Fe b Cu c Al d In (OH)2, 0.3≤a≤0.8, 0.2≤b≤0.4, 0.1≤c≤0.2, 0.1≤c≤0.2.

[0014] For example, a may be 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, b may be 0.2, 0.25, 0.3, 0.35 or 0.4, c may be 0.1, 0.13, 0.15, 0.18 or 0.2, and d may be 0.1, 0.13, 0.15, 0.18 or 0.2.

[0015] In a second aspect, the present invention provides a method for preparing the sodium ion precursor material as described in the first aspect, the preparation method comprising the following steps:

[0016] Adding a nickel-iron mixed salt solution, a copper salt solution, an aluminum salt solution, a precipitant solution and a first complexing agent solution to the bottom liquid in parallel for a coprecipitation reaction to obtain the sodium ion precursor material;

[0017] Wherein, the copper salt solution includes a second complexing agent; and the base solution is subjected to a deoxidation treatment.

[0018] The present invention adopts a coprecipitation method to prepare a sodium ion precursor material with uniformly distributed elements and stable structure. During the preparation process, a deoxidation treatment is performed in the base liquid to avoid oxidation of metal ions during the coprecipitation process. At the same time, aluminum salt and copper salt affect each other to avoid copper segregation and aluminum forming a separate phase. At the same time, a second complexing agent is added to the copper salt to obtain a copper complex solution, which plays a role in stabilizing the copper element. If the second complexing agent solution is not added to the copper salt solution, uniform coprecipitation of the copper element cannot be achieved.

[0019] Preferably, the molar concentration of the nickel-iron mixed salt solution is 0.1-5 mol / L, for example, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L.

[0020] Preferably, the nickel salt in the nickel-iron mixed salt solution includes any one of nickel sulfate, nickel nitrate or nickel chloride, or a combination of at least two of them.

[0021] Preferably, the iron salt in the nickel-iron mixed salt solution is any one of ferrous sulfate, ferrous nitrate or ferrous chloride, or a combination of at least two of them.

[0022] Preferably, the second complexing agent in the copper salt solution includes any one of ammonia water, sodium fluoride, sodium citrate, sodium lactate, disodium EDTA or sodium pyrophosphate, or a combination of at least two thereof.

[0023] In the present invention, the copper salt and the second complexing agent are first complexed to obtain a stable copper solution, which is conducive to forming a uniform coprecipitation compound during the coprecipitation reaction process.

[0024] Preferably, the molar ratio of the second complexing agent to copper in the copper salt solution is (1-4):1, for example, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1.

[0025] In the present invention, if the molar ratio of the second complexing agent to copper in the copper salt solution is too small, that is, too little second complexing agent is added, the complexing effect of the copper solution will be affected, while if the molar ratio is too large, that is, too much second complexing agent is added, too many impurities will be introduced into the coprecipitation system, increasing the engineering workload of the subsequent impurity removal process.

[0026] Preferably, the aluminum salt solution comprises aluminum sulfate solution and / or sodium aluminate solution, preferably sodium aluminate solution.

[0027] In the preparation method provided by the present invention, sodium aluminate is selected as the aluminum salt, which can better achieve the co-precipitation of the aluminum phase, while other types of aluminum salts, such as aluminum sulfate, may cause aluminum phase segregation, affecting the uniformity of precipitation.

[0028] Preferably, the aluminum salt solution is a sodium aluminate solution, which also includes a third complexing agent.

[0029] In the present invention, a complexing agent is added to the sodium aluminate solution to form an aluminum salt complex, which interacts with the copper salt complex to ensure uniformity and stability of the coprecipitation.

[0030] Preferably, the molar concentration of the third complexing agent in the aluminum salt solution is 0.1-1 mol / L, for example, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L.

[0031] In the present invention, the molar concentration of the aluminum salt is not particularly limited, and the concentration of the third complexing agent can be ensured according to actual needs.

[0032] Preferably, the third complexing agent includes any one of ammonia water, sodium fluoride, sodium citrate, sodium lactate, disodium EDTA or sodium pyrophosphate, or a combination of at least two thereof.

[0033] Preferably, the precipitating agent comprises sodium hydroxide.

[0034] Preferably, the first complexing agent comprises aqueous ammonia.

[0035] Preferably, the pH value of the base solution is 7.5-12, for example, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5 or 12.

[0036] Preferably, the mass concentration of aqueous ammonia in the base liquid is 0.1-10 g / L, for example, 0.1 g / L, 0.5 g / L, 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L, etc.

[0037] The base liquid provided by the present invention can control the pH value and ammonia concentration within the above range by adjusting the amount of alkali solution and complexing agent added.

[0038] Preferably, the deoxidation treatment comprises physical deoxygenation and / or adding a reducing agent to the base liquid.

[0039] The physical deoxygenation in the present invention includes but is not limited to introducing high-purity nitrogen or using a deoxygenator to perform deoxygenation, etc., and the oxygen content can be controlled within a range where the metal ions are not easily oxidized.

[0040] Preferably, the coprecipitation reaction temperature is 25-65°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or 65°C.

[0041] Preferably, the pH value during the coprecipitation reaction is 7.5-12, for example, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5 or 12.

[0042] Preferably, the stirring speed of the coprecipitation reaction is 100-1500 rpm, for example, 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm or 1500 rpm, etc.

[0043] In the coprecipitation process of the present invention, a sodium ion precursor material with uniform element distribution and stable structure is obtained through the coordination of the above reaction parameters.

[0044] As a preferred technical solution, the preparation method comprises the following steps:

[0045] Adding a nickel-iron mixed salt solution with a molar concentration of 0.1 to 5 mol / L, a copper salt solution, a sodium aluminate solution, a precipitant solution and a first complexing agent solution in parallel to a base solution with a pH value of 7.5 to 12 and a mass concentration of ammonia water of 0.1 to 10 g / L, and performing a coprecipitation reaction at 25 to 65° C. and a stirring speed of 100 to 1500 rpm while maintaining the pH value at 7.5 to 12 to obtain the sodium ion precursor material;

[0046] The copper salt solution includes a second complexing agent, and the molar ratio of the second complexing agent to copper is (1-4):1; the sodium aluminate solution includes a third complexing agent with a molar concentration of 0.1-1 mol / L; and the base solution is subjected to deoxidation treatment.

[0047] In a third aspect, the present invention provides a sodium ion oxide positive electrode material, wherein the sodium ion oxide positive electrode material is obtained by mixing and sintering the sodium ion precursor material as described in the first aspect and a sodium source.

[0048] Preferably, the molar ratio of the sodium ion precursor material to the sodium in the sodium source is 1:(1-1.2), for example, 1:1, 1:1.05, 1:1.1, 1:1.15 or 1:1.2.

[0049] Preferably, the sintering temperature is 400-1300°C, for example, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C or 1300°C.

[0050] Preferably, the sintering time is 8 to 48 h, for example, 8 h, 12 h, 15 h, 18 h, 20 h, 23 h, 25 h, 28 h, 30 h, 33 h, 35 h, 38 h, 40 h, 43 h, 45 h or 48 h.

[0051] In a fourth aspect, the present invention further provides a sodium ion battery, comprising the sodium ion oxide positive electrode material as described in the third aspect.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) The nickel-iron-copper-aluminum hydroxide precursor material provided by the present invention has uniform element distribution, and the nickel-iron-copper-aluminum elements cooperate and interact with each other. The change in copper valence is used to increase the capacity of the material, while improving the air stability of the material. The introduction of aluminum elements can stabilize the lattice framework structure of the precursor material, thereby obtaining a layered oxide positive electrode material with good stability, thereby improving the cycle performance of the positive electrode material. The positive electrode material in the sodium ion battery is prepared from the precursor material provided by the present invention, and during the precursor preparation process, the aluminum salt is selected from a sodium aluminate solution with a third complexing agent, and the molar ratio of the copper salt to the second complexing agent is adjusted. The battery is subjected to a constant current charge and discharge test within 2.0-4.0V, the first three cycles are at a rate of 0.1C, and then the rate is adjusted to 1C. The capacity retention rate after 200 cycles can reach more than 89.1%.

[0054] (2) During the preparation process of the present invention, a deoxidation treatment is performed in the base liquid to avoid oxidation of metal ions during the coprecipitation process. At the same time, the aluminum salt and the copper salt interact with each other to avoid copper segregation and the formation of aluminum as a separate phase. At the same time, a second complexing agent is added to the copper salt, thereby obtaining a sodium ion precursor material with uniform element distribution and stable structure. DETAILED DESCRIPTION

[0055] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0056] Example 1

[0057] This embodiment provides a sodium ion precursor material, the chemical formula of which is Ni 0.6 Fe 0.2 Cu 0.1 Al 0.1 (OH)2.

[0058] The preparation method of the sodium ion precursor material is as follows:

[0059] (1) preparing a metal ion solution A with a total metal concentration of 0.6 mol / L, wherein the molar ratio of nickel and iron is 60:20, and the metal solutions of nickel and iron used are nickel sulfate and ferrous sulfate in sequence; preparing solution B, mixing aluminum sulfate and excess sodium hydroxide solution to prepare a sodium aluminate solution with a molar concentration of 0.3 mol / L, mixing the sodium aluminate solution with 0.3 mol / L ammonia water to obtain solution B; mixing 0.3 mol / L copper sulfate solution with 0.6 mol / L ammonia water to obtain solution C (the molar ratio of the second complexing agent to copper is 2:1);

[0060] (2) Before the reaction, a base liquid is prepared in a reaction container, and sodium hydroxide solution and ammonia water are added until the pH of the reaction base liquid is 9.5-10 and the ammonia concentration is 4 g / L. High-purity nitrogen gas with a purity of 99.999% needs to be continuously introduced until the end of the reaction. Solution A, solution B and solution C are added to the base liquid at the same time according to the metal molar ratio of Ni:Fe:Cu:Al=6:2:1:1 to start the reaction. Ammonia water and liquid alkali are added at the same time. The pH value of the reaction process is controlled to be around 9.8 by using ammonia water and liquid alkali. The ammonia concentration is 4 g / L. The temperature during the reaction is controlled at 45°C and the stirring speed is controlled at 400 rpm. After the reaction particle size D50 of the quaternary precursor reaches 6 μm, the feeding is suspended. The obtained quaternary precursor solution is allowed to stand for 6 hours, and after washing, centrifugation, drying and other processes, it is dried in a vacuum freeze dryer for 12 hours to obtain the sodium ion precursor material Ni 0.6 Fe 0.2 Cu 0.1 Al 0.1 (OH)2.

[0061] Example 2

[0062] This embodiment provides a sodium ion precursor material, the chemical formula of which is Ni 0.3 Fe 0.3 Cu 0.2 Al 0.2 (OH)2.

[0063] The preparation method of the sodium ion precursor material is as follows:

[0064] (1) preparing a metal ion solution A with a total metal concentration of 0.6 mol / L, wherein the molar ratio of nickel and iron is 1:1, and the nickel and iron metal solutions used are nickel sulfate and ferrous sulfate in sequence; preparing a solution B, mixing aluminum sulfate and an excess of sodium hydroxide solution to prepare a sodium aluminate solution with a molar concentration of 0.5 mol / L, mixing the sodium aluminate solution with 0.5 mol / L ammonia water to obtain a solution B; mixing a 0.5 mol / L copper sulfate solution with 0.5 mol / L ammonia water to obtain a solution C (the molar ratio of the second complexing agent to copper is 1:1);

[0065] (2) Before the reaction, a base liquid is prepared in a reaction container, and sodium hydroxide solution and ammonia water are added until the pH of the reaction base liquid is 9.5-10 and the ammonia concentration is 6 g / L. High-purity nitrogen gas with a purity of 99.999% needs to be continuously introduced until the end of the reaction. Solution A, solution B and solution C are added to the base liquid at the same time according to the metal molar ratio of Ni:Fe:Cu:Al=3:3:2:2 to start the reaction. Ammonia water and liquid alkali are added at the same time. The pH value of the reaction process is controlled to be around 11 by using ammonia water and liquid alkali. The ammonia concentration is 5 g / L. The temperature during the reaction is controlled at 65°C and the stirring speed is controlled at 250 rpm. After the reaction particle size D50 of the quaternary precursor reaches 5 μm, the feeding is suspended. The obtained quaternary precursor solution is allowed to stand for 6 hours, and after washing, centrifugation, drying and other processes, it is dried in a vacuum freeze dryer for 12 hours to obtain the sodium ion precursor material Ni 0.3 Fe 0.3 Cu 0.2 Al 0.2 (OH)2.

[0066] Example 3

[0067] This embodiment provides a sodium ion precursor material, the chemical formula of which is Ni 0.6 Fe 0.2 Cu 0.1 Al 0.1 (OH)2.

[0068] The preparation method of the sodium ion precursor material is as follows:

[0069] (1) preparing a metal ion solution A with a total metal concentration of 0.6 mol / L, wherein the molar ratio of nickel and iron is 60:20, and the nickel and iron metal solutions used are nickel sulfate and ferrous sulfate in sequence; preparing a solution B, mixing aluminum sulfate and an excess of sodium hydroxide solution to prepare a sodium aluminate solution with a molar concentration of 0.3 mol / L, and mixing the sodium aluminate solution with 0.3 mol / L ammonia water to obtain a solution B; mixing a 0.3 mol / L copper sulfate solution with 1.2 mol / L sodium fluoride (a second complexing agent) to obtain a solution C (the molar ratio of the second complexing agent to copper is 4:1);

[0070] (2) Before the reaction, a base liquid is prepared in a reaction container, and sodium hydroxide solution and ammonia water are added until the pH of the reaction base liquid is 8 and the ammonia concentration is 2 g / L. High-purity nitrogen gas with a purity of 99.999% needs to be continuously introduced until the end of the reaction. Solution A, solution B and solution C are added to the base liquid at the same time according to the metal molar ratio of Ni:Fe:Cu:Al=6:2:1:1 to start the reaction. Ammonia water and liquid alkali are added at the same time. The pH value of the reaction process is controlled to be around 8 by using ammonia water and liquid alkali. The ammonia concentration is 2 g / L. The temperature during the reaction process is controlled at 45°C and the stirring speed is controlled at 400 rpm. After the reaction particle size D50 of the quaternary precursor reaches 6 μm, the feeding is suspended. The obtained quaternary precursor solution is allowed to stand for 6 hours, and after washing, centrifugation, drying and other processes, it is dried in a vacuum freeze dryer for 12 hours to obtain the sodium ion precursor material Ni 0.6 Fe 0.2 Cu 0.1 Al 0.1 (OH)2.

[0071] Example 4

[0072] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, solution B is an aluminum sulfate solution and does not contain ammonia water.

[0073] The rest of the preparation methods and parameters were the same as those in Example 1.

[0074] Example 5

[0075] The difference between this embodiment and embodiment 1 is that the sodium aluminate solution in step (1) of this embodiment does not contain ammonia water (the third complexing agent).

[0076] The rest of the preparation methods and parameters were the same as those in Example 1.

[0077] Example 6

[0078] The difference between this embodiment and embodiment 1 is that the molar concentration of aqueous ammonia in solution C in step (1) of this embodiment is 1.5 mol / L (the molar ratio of the second complexing agent to copper is 5:1).

[0079] The rest of the preparation methods and parameters were the same as those in Example 1.

[0080] Example 7

[0081] The difference between this embodiment and embodiment 1 is that the molar concentration of aqueous ammonia in solution C in step (1) of this embodiment is 0.15 mol / L (the molar ratio of the second complexing agent to copper is 0.5:1).

[0082] The rest of the preparation methods and parameters were the same as those in Example 1.

[0083] Comparative Example 1

[0084] The difference between this comparative example and Example 1 is that the second complexing agent is not added to the solution C in step (1) of this comparative example.

[0085] The rest of the preparation methods and parameters were the same as those in Example 1.

[0086] Comparative Example 2

[0087] The difference between this comparative example and Example 1 is that no copper salt solution is added during the preparation process of this comparative example, and the chemical formula of the sodium ion precursor material is Ni 0.7 Fe 0.2 Cu 0.1 (OH)2.

[0088] The rest of the preparation methods and parameters were the same as those in Example 1.

[0089] Comparative Example 3

[0090] The difference between this comparative example and Example 1 is that no copper salt solution is added during the preparation process of this comparative example, and the chemical formula of the sodium ion precursor material is Ni 0.7 Fe 0.2 Al 0.1 (OH)2.

[0091] The rest of the preparation methods and parameters were the same as those in Example 1.

[0092] The sodium ion quaternary precursors provided in Examples 1-7 and Comparative Examples 1-3 were mixed with sodium hydroxide in a ratio of 1:1.05, and calcined at 800°C for 24 hours to obtain a quaternary positive electrode material, and the material was mixed with SP (carbon black conductive agent), CNT (carbon nanotube), and PVDF (polyvinylidene fluoride), wherein the mass ratio of the material, SP+CNT, and PVDF was controlled to be 90:5:5, and NMP (N-methylpyrrolidone) was used as a solvent. After slurrying and stirring for several hours, the slurry was coated on the surface of an aluminum foil to obtain a sodium ion battery positive electrode sheet.

[0093] The positive electrode sheets provided in Examples 1-7 and Comparative Examples 1-3 were used as positive electrodes, the sodium sheets were used as counter electrodes, the negative electrodes in the half-cells used sodium metal as counter electrodes, and the electrolyte was 1 mol / L NaPF6 dissolved in a solvent of EC: PC: DMC = 1:1:1 (volume ratio). A button-type sodium battery was prepared, and the electrochemical performance of the battery was tested. A constant current charge and discharge test was performed within a voltage range of 2.0-4.0 V. The rate for the first three cycles was 0.1 C, and then the rate was 1 C. The test was performed for a total of 200 cycles to test the capacity retention rates of different materials. The test results are shown in Table 1.

[0094] Table 1

[0095] Capacity retention rate (%) Example 1 91.6 Example 2 93.4 Example 3 89.1 Example 4 66.7 Example 5 68.6 Example 6 78.9 Example 7 65.3 Comparative Example 1 61.2 Comparative Example 2 68.9 Comparative Example 3 63.7

[0096] It can be seen from the data results of Example 1 and Example 4 that when a non-sodium aluminate solution is used in the aluminum salt solution, the problem of aluminum phase segregation is likely to occur, thereby affecting the electrochemical properties of the material.

[0097] It can be seen from the data results of Example 1 and Example 5 that when sodium aluminate is used as the aluminum salt solution, if no third complexing agent is added, uneven precipitation of the aluminum phase will occur, affecting the cycle performance of the positive electrode material.

[0098] From the data results of Example 1 and Examples 6 and 7, it can be seen that in the copper salt solution, if the molar ratio of the second complexing agent to copper is too large, too many impurity phases will be introduced and thus affect the material properties, while if the molar ratio is too small, it will lead to incomplete copper phase complexation, which will also affect the final electrochemical properties.

[0099] It can be seen from the data results of Example 1 and Comparative Example 1 that if the second complexing agent is not added to the copper salt solution, uniform coprecipitation of the copper phase in the system cannot be achieved, which affects the electrochemical performance of the positive electrode material.

[0100] From the data results of Example 1 and Comparative Examples 2 and 3, it can be seen that in the sodium ion precursor material, the copper and aluminum elements influence each other and cooperate with the nickel and iron elements to improve the structural stability of the positive electrode material and improve the material cycle performance.

[0101] In summary, the present invention prepares nickel-iron-copper-aluminum hydroxide precursor materials through a coprecipitation method, and the elements are evenly distributed. During the preparation process, the base liquid is subjected to a deoxidation treatment to avoid oxidation of metal ions during the coprecipitation process. At the same time, aluminum salts and copper salts influence each other to avoid copper segregation and the formation of aluminum as a single phase. At the same time, a second chelating agent is added to the copper salt to make the elements evenly distributed. The nickel-iron-copper-aluminum elements cooperate and interact with each other, and the valence change of copper is used to increase the capacity of the material, while improving the air stability of the material. The introduction of aluminum elements can stabilize the lattice framework structure of the precursor material, thereby obtaining a layered oxide positive electrode material with good stability, thereby improving the cycle performance of the positive electrode material. The positive electrode material in the battery is prepared from the precursor material provided by the present invention, and in the precursor preparation process, the aluminum salt is selected from a sodium aluminate solution with a third complexing agent, and the molar ratio of the copper salt to the second complexing agent is adjusted. The battery is subjected to a constant current charge and discharge test within 2.0-4.0V, the rate for the first three cycles is 0.1C, and then the rate is adjusted to 1C. The capacity retention rate after 200 cycles can reach more than 89.1%.

[0102] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A sodium ion precursor material, characterized in that: The sodium ion precursor material includes nickel-iron-copper-aluminum hydroxide; The chemical formula of the nickel-iron-copper-aluminum hydroxide is Ni a Fe b Cu c Al d (OH)2, where 0.3≤a≤0.8, 0<b≤0.5, 0<c≤0.5, 0<d≤0.3, a+b+c+d=1; The precursor material is prepared by the following method, which comprises the following steps: Adding a nickel-iron mixed salt solution, a copper salt solution, an aluminum salt solution, a precipitant solution and a first complexing agent solution to the bottom liquid in parallel for a coprecipitation reaction to obtain the sodium ion precursor material; Wherein, the copper salt solution includes a second complexing agent; the base solution is subjected to a deoxidation treatment; The molar ratio of the second complexing agent to copper in the copper salt solution is (1-4):1; The aluminum salt solution is a sodium aluminate solution, which also includes a third complexing agent.

2. The sodium ion precursor material according to claim 1, characterized in that The Ni a Fe b Cu c Al d In (OH)2, 0.3≤a≤0.8, 0.2≤b≤0.4, 0.1≤c≤0.2, 0.1≤d≤0.

2.

3. A method for preparing a sodium ion precursor material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: Adding a nickel-iron mixed salt solution, a copper salt solution, an aluminum salt solution, a precipitant solution and a first complexing agent solution to the bottom liquid in parallel for a coprecipitation reaction to obtain the sodium ion precursor material; Wherein, the copper salt solution includes a second complexing agent; the base solution is subjected to a deoxidation treatment; The molar ratio of the second complexing agent to copper in the copper salt solution is (1-4):1; The aluminum salt solution is a sodium aluminate solution, which also includes a third complexing agent.

4. The method for preparing the sodium ion precursor material according to claim 3, characterized in that: The molar concentration of the nickel-iron mixed salt solution is 0.1-5 mol / L.

5. The method for preparing the sodium ion precursor material according to claim 3, characterized in that: The nickel salt in the nickel-iron mixed salt solution includes any one of nickel sulfate, nickel nitrate or nickel chloride, or a combination of at least two of them.

6. The method for preparing the sodium ion precursor material according to claim 3, characterized in that: The iron salt in the nickel-iron mixed salt solution is any one of ferrous sulfate, ferrous nitrate or ferrous chloride, or a combination of at least two of them.

7. The method for preparing the sodium ion precursor material according to claim 3, characterized in that: The second complexing agent in the copper salt solution includes any one of ammonia water, sodium fluoride, sodium citrate, sodium lactate, disodium EDTA or sodium pyrophosphate, or a combination of at least two thereof.

8. The method for preparing a sodium ion precursor material according to claim 3, characterized in that: The molar concentration of the third complexing agent in the aluminum salt solution is 0.1-1 mol / L.

9. The method for preparing a sodium ion precursor material according to claim 3, characterized in that: The third complexing agent includes any one of ammonia water, sodium fluoride, sodium citrate, sodium lactate, disodium EDTA or sodium pyrophosphate, or a combination of at least two thereof.

10. The method for preparing a sodium ion precursor material according to claim 3, characterized in that: The precipitating agent includes sodium hydroxide.

11. The method for preparing a sodium ion precursor material according to claim 3, characterized in that: The first complexing agent includes aqueous ammonia.

12. The method for preparing a sodium ion precursor material according to claim 3, characterized in that: The pH value of the base liquid is 7.5-12.

13. The method for preparing a sodium ion precursor material according to claim 12, characterized in that: The mass concentration of ammonia water in the base liquid is 0.1-10 g / L.

14. The method for preparing a sodium ion precursor material according to claim 3, characterized in that: The deoxidation treatment includes physical deoxidation and / or adding a reducing agent to the base liquid.

15. The method for preparing a sodium ion precursor material according to claim 3, characterized in that: The temperature of the coprecipitation reaction is 25-65°C.

16. The method for preparing a sodium ion precursor material according to claim 3, characterized in that: The pH value during the coprecipitation reaction is 7.5-12.

17. The method for preparing a sodium ion precursor material according to claim 3, characterized in that: The stirring speed of the coprecipitation reaction is 100-1500 rpm.

18. The method for preparing a sodium ion precursor material according to claim 3, characterized in that: The preparation method comprises the following steps: Adding a nickel-iron mixed salt solution with a molar concentration of 0.1 to 5 mol / L, a copper salt solution, a sodium aluminate solution, a precipitant solution and a first complexing agent solution in parallel to a base solution with a pH value of 7.5 to 12 and a mass concentration of ammonia water of 0.1 to 10 g / L, and performing a coprecipitation reaction at 25 to 65° C. and a stirring speed of 100 to 1500 rpm while maintaining the pH value at 7.5 to 12 to obtain the sodium ion precursor material; The copper salt solution includes a second complexing agent, and the molar ratio of the second complexing agent to copper is (1-4):1; the sodium aluminate solution includes a third complexing agent with a molar concentration of 0.1-1 mol / L; and the base solution is subjected to deoxidation treatment.

19. A sodium ion oxide positive electrode material, characterized in that: The sodium ion oxide positive electrode material is obtained by mixing and sintering the sodium ion precursor material as claimed in claim 1 or 2 and a sodium source.

20. The sodium ion oxide positive electrode material according to claim 19, characterized in that: The molar ratio of the sodium ion precursor material to the sodium in the sodium source is 1:(1-1.2).

21. The sodium ion oxide positive electrode material according to claim 19, characterized in that: The sintering temperature is 400-1300°C.

22. The sodium ion oxide positive electrode material according to claim 19, characterized in that The sintering time is 8 to 48 hours.

23. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion oxide positive electrode material as described in any one of claims 19-22.